Effect of Cyber Security on Business Sustainability of Listed Microfinance Banks in Nigeria - Nwankwo, Cosmas Anayochukwu; Kanyangale, Macdonald Isaac (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: In Nigeria, microfinance banks (MFB) face the burden of investing in cyber security to protect their databases, prevent monetary losses, maintain customer trust, and remain afloat in a competitive business environment. However, there are incessant cyber risks and attacks by criminals who gain undue access to the cyber-space of MFB and cause financial and non-financial loss. Design/methodology/approach: The objective of this quantitative study was to examine the effect of cyber security on the business sustainability of three listed, and most valued MFBs in Nigeria. The population of the study was 315 senior, medium and junior employees of three MFBs in Nigeria. As the target population was manageable, the research adopted a census. Data were collected using a semi-structured questionnaire, and the formulated hypothesis was analysed using multiple regression. Findings: The study found that cyber security has a significant and positive impact on the sustainability of MFB in Nigeria. Data availability account for the largest contribution to the sustainability of MFBs, followed by data confidentiality and data integrity. Employees in a MFB uphold that data availability, confidentiality, and integrity are pivotal elements of cyber security that influence the sustainability of their organisations in Nigeria. Given these results from the viewpoint of employees, MFBs are implored to regularly review and strengthen their risk management strategy and adopt a more integrative approach of human-centric cybersecurity, which brings technology and human elements together to address current and future cyber risks and build and sustain consumer trust in digital financial transactions. The implication of the study and areas for future research are highlighted. Paper type: Research paper